DETERMINATION OF SOIL OVERCONSOLIDATION AT FARM UNITS OF WESTERN PART OF UKRAINIAN FOREST-STEPPE - Іванишин В.В., В. В.; Рудь, А. В.; Мошенко, І. О. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
The paper reports on research into reducing soil fertility due to irrational application of intensive technologies, energy means, technological machines and aggregates that destroy the soil, intensify water and wind erosion. The paper concentrates on negative influence of multiple displacements of machine and tractor aggregates at the field that leads to soil panning. The prevention measures for preconsolidation caused by machine and tractor undercarriage are proposed. We consider the process of plough-pan formation, its negative influence on crops, prevention measures for plough-pan formation and its destroying. The study investigates this issue by applying the research method of overconsolidated soil studying with the help of consistometers of spring, shock and manual type made by Eijkelkamp Agrisearch Equipment (the Netherlands). The article provides the scheme of monogram for transferring the manometer DICKEJ-john penetrometer characteristics in PSI (psi per square inch) in metric measure unit. The critical values of penetration resistance of the soil that causes the difficulties in root penetrating in the soil are determined; a visual characteristic of the soil in terms of different soil density is given. Number and quality parameters of soil density are identified. The results of the study of the spatial variation of soil penetration resistance at the fields of Scientific and Production Centre of State Agrarian and Engineering University in Podilya in March, 2017 are presented